A Double-Tuned Pendulum Mass Damper Employing a Pounding Damping Mechanism for Vibration Control of High-Rise Structures. (18th April 2023) - Wang, Wenxi; Yu, Tianfu; Yang, Zhilin; Zhang, Hongyi; Hua, Xugang
Abstract : Recently, enhancing conventional tuned mass dampers (TMDs) with a pounding damping mechanism is demonstrated to be an efficient way for vibration control of flexible structures. In this paper, a double-tuned pendulum mass damper employing a pounding damping mechanism (DTPMD-PD) is proposed. DTPMD-PD dissipates energy through the collision between distributed balls with a smaller mass and viscoelastic (VE) boundary, which can effectively reduce noise during operation compared to conventional impact dampers. Moreover, DTPMD-PD utilizes a double-tuning mechanism, and its control performance is significantly enhanced. The motion equations of a multiple degree of freedom (MDOF) structure equipped with DTPMD-PD are formulated. Based on the H ∞ optimization criterion, a numerical optimization is performed to obtain the optimal design parameters of DTPMD-PD. Additionally, the pounding dissipation capacity and the parametric identification of the impact force model are investigated through free pounding experiments, and the control performance and robustness of DTPMD-PD are experimentally studied in the laboratory. The results show that the proposed numerical modeling method has considerable accuracy through experimental verifications. The restitution coefficient of the pounding layer has a significant influence on the performance of proposed DTPMD-PD. Optimized DTPMD-PD has better effectiveness than conventional TMDs under harmonic and seismic loads.